COMPARISON OF EFFECT OF HIORA MOUTHWASH VERSUS CHLORHEXIDINE MOUTHWASH IN GINGIVITIS PATIENTS: A CLINICAL TRIAL - Ramamurthy, Jaiganesh; Mg, Visha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim and objective of this study was to evaluate the effect of Hiora mouthwash versus Chlorhexidine mouthwash for the treatment of gingivitis. Methods: The study population was comprised 30 gingivitis patients. The patients were randomly categorized into two groups of 15 patients in each group. Group A was given Chlorhexidine mouthwash and Group B was given Hiora mouthwash. Pre-operative measurements such as plaque index (PI), gingival index (GI), and probing depth (PD), and loss of attachment (LA) were measured. Oral prophylaxis followed by the prescription of mouthwash was done. The patients were recalled for a review after 15 days, and post-operative measurements were recorded. Results: From the statistical analysis in the experimental Group A and Group B, the mean values of PD, LA, GI, and PI were found to be significantly lower in the post-operative period than the pre-operative mean values. At the end of 15 days, almost comparable reduction in the amount of plaque and gingivitis was found in both Group A and Group B. Hence, the differences in efficacy of these two mouthwashes were non-significant. Conclusion: Hiora and Chlorhexidine mouthwashes were equally effective in the treatment of gingivitis.